Principles and practice of expressive arts therapy : toward a therapeutic aesthetics - Knill, Paolo J. (Jessica Kingsley Publishers, 2005)
Challenging traditional therapeutic approaches to the arts in which art is often secondary to a psychological model, Principles and Practice of Expressive Arts Therapy provides a coherent theoretical framework for an expressive arts therapy practice that places the process of art-making and the art work itself at the center. This book lays the philosophical foundation for a fresh interpretation of art-making and the therapeutic process by re-examining the concept of poiesis. The authors clarify the methodology and theory of practice with a focus on intermodal therapy, crystallization theory an.